2015
DOI: 10.1016/j.wem.2015.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Field Ultrasound Evaluation of Central Volume Status and Acute Mountain Sickness

Abstract: Ultrasonography is a useful tool in the assessment of intravascular volume at altitude. In this sample, we found ultrasonographic evidence that subjects with AMS have a higher intravascular volume than asymptomatic individuals. These data support the hypothesis that individuals with AMS have decreased altitude-related diuresis compared with asymptomatic individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Ultrasonography has been attempted as a clinical prognosticator at high altitudes [23] but with limited diagnostic success as a point estimate of AMS [24]. Similar to other high-altitude ultrasound studies [13], our results indicated that a single measurement of intravascular volume has limited applicability and is not a useful clinical adjunct to the evaluation and performance determinant of high-altitude mountaineers.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Ultrasonography has been attempted as a clinical prognosticator at high altitudes [23] but with limited diagnostic success as a point estimate of AMS [24]. Similar to other high-altitude ultrasound studies [13], our results indicated that a single measurement of intravascular volume has limited applicability and is not a useful clinical adjunct to the evaluation and performance determinant of high-altitude mountaineers.…”
Section: Discussionsupporting
confidence: 52%
“…Another objective measurement of hydration status is by ultrasound measurement of the IVC-CI during the respiratory cycle. This allows direct measurement of the vascular status and has been shown to reliably predict volume status in both emergency department patients and healthy cohorts in field clinics [13]. During inspiration, generated negative intrathoracic pressure and positive intra-abdominal pressure increases venous return and collapses the IVC.…”
Section: Introductionmentioning
confidence: 99%
“…The use of general anesthetics is associated with hypotension, which may lead to adverse outcomes. [37] Ultrasound can predict post-anesthesia hypotension by measuring the IVC CI and diameter A recent study [38] has also evaluated the utility of ultrasound in detecting volume status in the pre-hospital setting. Ultrasound showed that subjects with acute mountain sickness have greater intravascular volume than controls.…”
Section: Assessment Of Corrected Fl Ow Timementioning
confidence: 99%
“…Ultrasonography can also be used to determine total body fluid status in the field, most easily by measuring the inferior vena cava (IVC) collapsibility index (CI). Pitman et al used this technique in their study which compared volume status in high-altitude trekkers with symptoms of AMS to altitudematched controls without AMS (Pitman et al, 2015). The IVC CI evaluates a patient's IVC diameter throughout the respiratory cycle, comparing the smallest diameter to its largest by employing the use of M-mode on the ultrasound device.…”
Section: Vascularmentioning
confidence: 99%